A Combined Flume-imaging Technique for Measuring Fluvial Erosion of Cohesive Stream Bank Soils. (2015) - Sutarto, Tommy E.
Abstract: Less attention has been given to fluvial erosion even though, in many instances, it has been shown to affect stream bank stability by being a precursor to mass failure. As a result, the technique for measuring fluvial erosion parameters, most importantly the critical erosional strength, τc, is under-developed. The main objective of this study was to develop a laboratory technique using a state-of-the-art closed-conduit flume and imaging instrument for determining the τc, of cohesive bank soils. A total of 24 (twenty four) bank soil samples were extracted from the crest, midbank, and toe of a stream bank and tested for their c' and τc. using a standardized direct shear device and the combined flume-imaging technique, respectively. It was found that the methods can accurately determine c' and τc parameters. The c ' values were 2 to 4 orders of magnitude larger than the τc values. In addition, c' and τc values had increasing trend through the downslope of the stream bank highlights the need of acquiring both mechanical and erosional strengths for the three layers along a bank profile (namely crest, midbank, and toe) to improve the commonly adopted protocols that typically assume homogeneous bank soils.